The Relationship Between PSN Behavior with Existence Larvae of Aedes aegypti In Port of Pulang Pisau - Nani Nani (Jurnal Berkala Epidemiologi, 2017)
The existence of Aedes aegypti larvae is an indicator of the presence of Aedes aegypti mosquito populations in the region. The most effective effort to eradicate larvae is carrying out activities to Mosquito Source Reduction (PSN). This study aims to analyze the relationship of knowledge, attitudes, and actions of PSN with the existence of Aedes aegypti. This research was an observational analytic study with a cross-sectional study design with a sample size of 80 respondents selected by simple random sampling. This research was conducted at Pulang Pisau Port, class III Port Health Office, Palangkaraya in September-December 2016. The independent variables studied were PSN knowledge, attitudes, and actions, while the dependent variable was the existence of Aedes aegypti larvae. Data collection using interview techniques and observation sheets of the existence of Aedes aegypti larvae. Data analysis using the chi-square test. The results of this study indicate that there is a significant relationship between knowledge (p = 0.004; PR = 1.76; 95% CI = 1.19–2.59), attitude (p = 0.024; PR = 1.55; 95% CI = 1.08–2.24) and PSN actions (p = 0,000; PR = 3.89; 95% CI = 2.01–7.52) with the presence of Aedes aegypti larva. The conclusion of this study is that there is a relationship between the knowledge, attitudes, and actions of PSN with the existence of Aedes aegypti larvae in the Pulang Pisau Port working area.